2014
DOI: 10.1016/j.drudis.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing the BMPR2 signaling axis in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a lethal disorder characterized by pulmonary arterial remodeling, increased right ventricular systolic pressure (RVSP), vasoconstriction and inflammation. The heritable form of PAH (HPAH) is usually (>80%) caused by mutations in the bone morphogenic protein receptor 2 (BMPR2) gene. Existing treatments for PAH typically focus on the end-stage sequelae of the disease, but do not address underlying mechanisms of vascular obstruction and blood flow and thus, in the long run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…80%) caused by mutations in the BMPR2 . 7 In animal models, it has been shown that greater endothelial injury and enhanced infl ammatory response could be the underlying causes of the sensitivity and may work in concert with BMPR2 heterozygosity to promote the development of persistent pulmonary hypertension. 8 Diff erent studies have shown increased levels of cytokines in PAH, including the proinfl ammatory cytokines IL-1 b , IL-2, IL-4, IL-6, IL-8, IL-12p70, tumor necrosis factor (TNF)-a , monocyte chemoattractant protein-1, 9,10 and the cytokine-like hormone leptin.…”
mentioning
confidence: 99%
“…80%) caused by mutations in the BMPR2 . 7 In animal models, it has been shown that greater endothelial injury and enhanced infl ammatory response could be the underlying causes of the sensitivity and may work in concert with BMPR2 heterozygosity to promote the development of persistent pulmonary hypertension. 8 Diff erent studies have shown increased levels of cytokines in PAH, including the proinfl ammatory cytokines IL-1 b , IL-2, IL-4, IL-6, IL-8, IL-12p70, tumor necrosis factor (TNF)-a , monocyte chemoattractant protein-1, 9,10 and the cytokine-like hormone leptin.…”
mentioning
confidence: 99%
“…Histological evidence suggests markedly downregulated BMPR2 expression in the pulmonary vasculature of patients with mutations and moderately decreased BMPR2 expression in that of IPAH patients even without known mutations [8], suggesting deficiency of BMPR2 signaling may be a wider phenomenon beyond HPAH. Premature terminations result in the activation of the nonsense-mediated decay pathway and cause disease due to functional haploinsufficiency [143,212]. On the other hand, amino acid substitutions may lead to loss of kinase activity and aberrant trafficking of misfolded BMPR2 in the endoplasmic reticulum and cause disease by dominantnegative effects [60,212].…”
Section: Effect Of Mutations On Expression and Activity Of Bmpr2mentioning
confidence: 97%
“…Premature terminations result in the activation of the nonsense-mediated decay pathway and cause disease due to functional haploinsufficiency [143,212]. On the other hand, amino acid substitutions may lead to loss of kinase activity and aberrant trafficking of misfolded BMPR2 in the endoplasmic reticulum and cause disease by dominantnegative effects [60,212]. Some BMPR2 mutants may reach the cell membrane but form clusters or otherwise exhibit altered associations with membrane domains, including caveolae, lipid rafts, or clathrin-coated pits [94].…”
Section: Effect Of Mutations On Expression and Activity Of Bmpr2mentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in this gene have been involved in multiple signaling pathways implicated in the development of PH. Our current understanding of BMPR2 regulation suggests that although 80% of familial PH is caused by a BMPR2 mutation, almost all forms of PH share abnormal BMPR2 signaling [44**]. …”
Section: Introductionmentioning
confidence: 99%